2019
DOI: 10.1111/cpr.12667
|View full text |Cite
|
Sign up to set email alerts
|

An extravascular fluid transport system based on structural framework of fibrous connective tissues in human body

Abstract: Objective: Interstitial fluid in extracellular matrices may not be totally fixed but partially flow through long-distance oriented fibrous connective tissues via physical mechanisms. We hypothesized there is a long-distance interstitial fluid transport network beyond vascular circulations. Materials and methods:We first used 20 volunteers to determine hypodermic entrant points to visualize long-distance extravascular pathway by MRI. We then investigated the extravascular pathways initiating from the point of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(57 citation statements)
references
References 24 publications
3
52
0
2
Order By: Relevance
“…To further confirm the universal existence of the above discoveries in the whole body, the human cadavers were used to testify the extravascular pathways by the simulated heart pulsation using a mechanical chest compressor. 14 The perivascular pathways from the thumb were observed along the veins of the arm, axillary sheath, superior vena cava and in the superficial tissues on the right atrium. Histological and micro-CT (a higher resolution) data showed that these long-distance pathways were neither blood nor lymphatic vessels but the fibrous connective tissues, in which the micron-sized fibres were longitudinally assembled from the thumb to the superficial tissues on the right atrium and appendage.…”
Section: The Anatomical and Histological Structures Of An Extravascmentioning
confidence: 99%
See 3 more Smart Citations
“…To further confirm the universal existence of the above discoveries in the whole body, the human cadavers were used to testify the extravascular pathways by the simulated heart pulsation using a mechanical chest compressor. 14 The perivascular pathways from the thumb were observed along the veins of the arm, axillary sheath, superior vena cava and in the superficial tissues on the right atrium. Histological and micro-CT (a higher resolution) data showed that these long-distance pathways were neither blood nor lymphatic vessels but the fibrous connective tissues, in which the micron-sized fibres were longitudinally assembled from the thumb to the superficial tissues on the right atrium and appendage.…”
Section: The Anatomical and Histological Structures Of An Extravascmentioning
confidence: 99%
“…15 The ITZ is not an interface of a few molecular layers but contains a thin, probably a nanometre-thickness space paved on a solid surface. 14…”
Section: An Interfacial Transport Zone Within Interstitial Matricesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in acupuncture, functional magnetic resonance imaging studies are increasingly being conducted to delineate areas of brain activation with needle placement and have revealed several differences between true and sham acupuncture 42. Investigations using cadavers and animal models have also helped explain how distal acupoints may modulate pain responses 43 44. Despite this increasing evidence, concerns that acupuncture may simply be a placebo continue to dominate the conversation 45…”
Section: Discussionmentioning
confidence: 99%